The Impact of Organizational Climate on the Performance of Islamic Banks in Yemen: A Field Study - Al-Ahmadi, Nasr Ali Hezam (University of Science and Technology Journal for Management and Human Sciences, 2024)
This study aimed to investigate the impact of organizational climate, represented by two dimensions (communication and participation in decision-making), on the performance of Islamic banks in Yemen. The analytical approach was employed, utilizing a questionnaire as the primary tool for data collection and analysis using the SPSS statistical program. The study targeted the five Islamic banks in Yemen, with a total of 2864 employees across all organizational levels. The targeted sample size was 340 individuals. The findings revealed there is a statistically significant impact of organizational climate on organizational performance in Islamic banks in Yemen, through its two dimensions (communication and participation in decision-making), where the most influential dimension was the (participation in decision-making), followed by the (communication). The study recommends that Islamic banks in Yemen pay greater attention to fostering an organizational climate that is conducive and suitable, leading to employee satisfaction and contributing to outstanding performance at both the individual and bank levels.
Keywords: organizational climate; organizational performance; Islamic banks operating in Yemen